Art : an A-Z guide - Greenway, Shirley (Danbury, Conn. : F. Watts, 2000)
A dictionary of terms and concepts related to art history and art techniques, including artists and schools of art.
"Produced in association with ticktock publishing ltd."--T.p. verso.
Includes index.
Wilson's Junior High School.
8.1
5-8
Keywords: Art -- Dictionaries, Juvenile; Art -- History -- Dictionaries, Juvenile; Art -- Dictionaries; Art -- History -- Dictionaries; Art -- Dictionaries; Art -- History -- Dictionaries